Disabling Africa: the power of depiction and the benefits of discomfort. Issue 3 (16th March 2018) - Swartz, Leslie; Marchetti-Mercer, Maria
Abstract: Despite the fact that the vast majority of disabled people live in low and middle-income countries, the field of disability studies is dominated by research on disability in wealthy contexts. Although there are encouraging signs of this pattern changing, there are challenges to researchers about how to represent and think about disability in African contexts, and it is difficult not to reproduce unhelpful stereotypes. We use the example of an encounter we had with an expatriate Deaf South African to reflect on the complexities of representation facing people working on disability issues in Africa and what has been termed the Global South. We suggest that an appreciation of the productive value of discomfort about issues of representation may help move the field forward.